THE POSITION OF UNITED KINGDOM TOWARDS DIPLOMATIC ASYLUM OF JULIAN ASSANGE - Dwi Ajeng Zahrotun Noor (HI 16 UMY 042, 2016)
*42 This paper examines the position of United Kingdom towards diplomatic asylum of Julian Assange. This problem started when Ecuador decided to guarantee diplomatic asylum to Julian Assange. The Ecuadorian decision by guaranteeing diplomatic asylum to Assange harmed the position of United Kingdom since it interdicted the judicial process of United Kingdom. Meanwhile, the United Kingdom had legal obligation to extradite Assange to Sweden under the law of United Kingdom and international law. However, the United Kingdom could not interdict Ecuadorian decision. This phenomenon happened because of the existent of international regimes in international politics. In this case, international law recognize as international regime since it provides norms, principles, rules and decision-making procedures. There are two factors unable United Kingdom to interdict Ecuadorian decision which is the humanitarian principle and Vienna Convention on Diplomatic Relations (1961).